Agrifood value chains in India: A state-level analysis using a social accounting matrix - Pal, Barun Deb; Thurlow, James; Pauw, Karl; Diao, Xinshen; Ajmani, Manmeet Singh (International Food Policy Research Institute, 2025)
This study describes disparities in per capita income, in the structure of the economy, and in agrifood systems (AFS) across states in India. We use the gross value added (GVA) obtained from state-specific agrifood value chains (AVCs) to describe the size and structure of the AFS in each state of India. This study also presents the size of employment and variability in labor productivity within the AFS across states. A special focus is given to female and youth employment in the state specific AVCs. The 2017/18 state-level social accounting matrix (SAM) for India is the primary data source for estimating statewise GVA from the AFS. Periodic Labor Force Survey data are used to estimate the size of AFS employment. Our results reveal that the bottom half of the Indian population has an average per capita income of US$1,019, 2.5 times lower than that of the top half. India’s AFS is valued at $756 billion, or 31 percent of its GVA. Primary agriculture comprises 59 percent of the AFS, and off-farm activities the rest. The share of off-farm activities in the AFS rises moving from lower-income states to higher-income states, corroborating the theory of structural transformation. The national average share of female workers in total employment is 23 percent and the majority of women who do work are engaged in primary agriculture. The share of women employed in the primary agriculture sector does not change between low- and high-income states in India. In contrast, the share of youth in primary agriculture declines between lower- and higher-income states. Since state governments in India are empowered to design their own policy and development strategies, this study provides an important policy insight to both the federal (central) and state governments.